Methodological Support of Organizations Implementing Innovative Activities Investment Attractiveness Estimation - PLASKOVA, Nataliya S.; PRODANOVA, Natalia A.; ZATSARINNAYA, Еlena I.; KORSHUNOVA, Lyudmila N.; CHUMAKOVA, Natalya V. (Journal of Advanced Research in Law and Economics, 2018)
Development of modern economy in the context of globalization and business integration, competition stiffening in virtually all sectors of the national economy, makes it impossible to develop large enterprises without significant investment infusions. Therefore, the topic is relevant and necessary for consideration. The main goal of the work is to disclose various aspects of methodological support for assessing the investment attractiveness of innovative companies that are necessary to meet the information needs of their owners, investors, grant holders, and financial professionals. To achieve this goal, the authors used methods of analysis and synthesis. The authors clarified the definition and essence of the ‘investment attractiveness’ concept and structured the analytical characteristics and indicators of the organization’s investment attractiveness. A critical review of the existing methods of analyzing the investment attractiveness of organizations made it possible to identify their advantages and disadvantages, adapt existing methods taking into account the innovative features of companies developing intellectual products. It was proposed universal methodology for rating the investment attractiveness of companies that carry out innovation activities.